All natural bioadhesives - Wu, Vicki Xinyi (Nanyang Technological University, 2022)
The traction that bioadhesives have gained over the years has been increasing due to recent developments of finding an alternative to traditional suturing. The use of bioadhesives is applicable across fields in wound closure, tissue engineering, drug delivery and even implantation of medical devices. However, bioadhesives in the market be it synthetically derived or naturally derived do have their shortcomings. Synthetic bioadhesives often lack biocompatibility. Moreover, in the field of natural bioadhesives, there is a lack of natural bioadhesives providing with high adhesion strength. This project exploits the advantage of natural derived components’ good biocompatibility to formulate an all-natural bioadhesives with high adhesion strength. In this report, the structure property relationships of these naturally derived components will be covered. The reason for the chosen components used are: Tannic Acid, Polyamines – putrescine, spermidine & spermine, Lithium Lipoate will be explored in this report. The formulation will optimize the ratio of these components to achieve the highest adhesion strength. The lap shear adhesion strength increases with the number of amine groups present in the polyamine. The optimum formulation of Putrescine producing the highest adhesion strength obtained is 45.03kPa; Spermidine producing the highest adhesion strength obtained is 49.50kPa; Spermine producing the highest adhesion strength obtained is 60.73kPa. Although, the highest adhesion strength obtained is still not satisfactory (< 50kPa), the structure-activity relationship presented in this report highlights potential for improvement upon further research using other naturally derived components in hopes of obtaining higher adhesion strength.